(untitled) (Baghdad Science Journal, 2012)
The quantitative determination of the estrogen E2, Progestron P4 & follicle stimulating hormones FSH in the serums of Albino mice used in the experiments & treated by crude alcoholic extracted 95% of the seeds & leaves of Apium graveolens was a significant increase in the concentration of estrogen of different kinds of the extracted in comparison with the values of the coefficient of the control group, that is the study recorded a significant increase of the concentration of estrogen; it was the highest in the mice which was administrated by the methanolic extracted 95%, then it was less in the mouse which was administrated by the ethanolic extracted., and it was the least in the mice which were administrated by the crude ethanolic-methanoloic extracted of the seeds of Apium graveolens; while the increase of the concentration of estrogen of different crude alcoholic extracted leaves of Apium graveolens was the highest than the extracted of the seeds, & it was less concentration in the mice which were administrated by the methanolic extracted 95%, & then it was the least in the mice which were administrated by the crude ethanolic-methanolic extracted leaves of Apium graveolens in comparison with the values of the control group. Further, the plant extracted created a significant increase of the concentration of progestron P4; the statistics analysis recorded that the concentration of progestron was the highest in the mice which were administrated by the methanolic extracted 95%, then it was less in the mice which were administrated by the ethanolic extracted 95%, and the least in the mice which were administrated by the crude ethanolic-methanolic extracted of the seeds of apium graveolens whereas, a significant increase of the concentration of progrstrone was recorded in the leaves of Apium graveolens as follows: it was the highest in the mice which were administrated by the ethanolic extracted 95%, then it was less in the mice which were administrated by the crude methanolic extracted 95%, and it was the least in the mice which were administrated by the crude ethnolic-methanolic extracted in comparison with the coefficient of control group. The study also proved that there was a significant increase of the concentration of the follicle stimulating hormone FSH whose greatest concentration in the mice which was administrated by the crude ethanolic-methanolic for the seeds of Apim graveolens, it was less concentration in the mice which was administrated by crude methanolic extracted 95% of the seeds, and it was the least in the mice which was administrated by the methanolic extracted 95% of the leaves of Apium graveolens in comparison with the concentrations of the coefficient of the control group. While, the results recorded a significant decrease of the FSH in the mice which was administrated by the crude ethanolic extracted of the seeds & leaves of Apium graveolens a highest decrease, it was less concentration in the mice which was administrated by the crude ethanolic-methanolic extracted of the leaves of apium graveolens, in comparison with the concentration in the control group.